Proposed Marketing Strategy XYZ to Increase Revenue In The Covid-19 Pandemic - Divani Rafitya Amanda; Ira Fachira; Budi Permadi Iskandar (Syntax Corporation, 2022)
XYZ is a semi fine dining restaurant with unique and thematic indoor-outdoor space concept, and a wide selection of Indonesian and Western food. During the COVID-19 Pandemic, the activity limitations enforced by the government and changing in consumer behaviour during the pandemic that affects XYZ’s revenues negatively. The problem that will be discussed in this research is regarding the decrease in revenue from direct customers of XYZ. Therefore, the discussion of this research focuses on making business proposals to create an effective marketing strategy for XYZ by optimizing their digital marketing. To propose the appropriate digital marketing strategy, the author analyzes the company's internal and external elements. Internal analysis is performed using STP Analysis and Marketing Mix 7Ps, whilst external analysis is performed using PEST Analysis, Porter’s Five Forces Analysis, and Porter’s Framework for Competitor Analysis. Furthermore, the author distributes questionnaires to existing customers of XYZ. Then, the author conducts Root Cause Analysis to identify the true cause of problem and conducts TOWS Matrix Analysis to propose solutions to its business issues. The result of this research is the author suggests six strategies for dealing with its business challenges, which is by actively create promotions on social media Instagram, optimizing social media Instagram, marketed XYZ as an indoor-outdoor venue, create photo competition campaign as requirement to participate product giveaway, expand the online channel by partnering with food delivery services provider as merchant, and create catchy banner advertisements to place it on Cibubur housing complex.